Perceptual response and information pick-up strategies within a family of sports - Ida, H.; Fukuhara, K.; Ishii, M.; Inoue, T. (Human Movement Science, 2013)
The purpose of this study was to determine whether and how the perceptual response of athletes differed depending on their sporting expertise. This was achieved by comparing the responses of tennis and soft tennis players. Twelve experienced tennis players and 12 experienced soft tennis players viewed computer graphic serve motions simulated by a motion perturbation technique, and then scaled their anticipatory judgments regarding the direction, speed, and spin of the ball on a visual analogue scale. Experiment 1 evaluated the player`s judgments in response to test motions rendered with a complete polygon model. The results revealed significantly different anticipatory judgments between the player groups when an elbow rotation perturbation was applied to the test serve motion. Experiment 2 used spatially occluded models in order to investigate the effectiveness of local information in making anticipatory judgments. The results suggested that the isolation of visual information had less effect on the judgment of the tennis players than on that of the soft tennis players. In conclusion, the domain of sporting expertise, including those of closely related sports, cannot only differentiate the anticipatory judgment of a ball`s future flight path, but also affect the utilization strategy for the local kinematic information.